Mapping Value Co-creation Literature in the Technology and Innovation Management Field: A Bibliographic Coupling Analysis - Nájera-Sánchez, Juan-José; Ortiz-de-Urbina-Criado, Marta; Mora-Valentín, Eva-María (Frontiers in Psychology, 2020)
Value co-creation has become a very important topic in several disciplines. It is observed that value co-creation has been analyzed mainly from a perspective of marketing or services. The interest of studying value co-creation in relation to innovation is growing but there are no previous literature reviews that focus on the literature that studies value co-creation from a technology and innovation management perspective. The present research aims to close this gap. This research has two aims. First, we make a descriptive analysis of the evolution of documents published from 2004 to 2020. We analyze the main journals and identify the most prolific authors. In addition, we observe collaborative behavior at three different levels – country, institution, and author. Second, we determine the content structure of this literature through a bibliographic coupling analysis, and characterize the resulting groups. As a result of this analysis, we describe eleven thematic groups and characterize them through different metrics. Based on these metrics and the previous analysis, we classify and explain the studies about co-creation in the technology and innovation management field. We obtained three research streams: open innovation, consumer-centric analysis, and service ecosystem and service innovation, and two new trends: servitization and the sharing economy.